Blue and Deep‐Blue‐Emitting Organic Lasers with Top‐Layer Distributed Feedback Resonators. Issue 24 (27th October 2020) - Bonal, Víctor; Villalvilla, José M.; Quintana, José A.; Boj, Pedro G.; Lin, Naiti; Watanabe, Shoya; Kazlauskas, Karolis; Adomeniene, Ona; Jursenas, Saulius; Tsuji, Hayato; Nakamura, Eiichi; Díaz‐García, María A.
Abstract: All‐solution processed surface‐emitting organic distributed feedback lasers are attractive devices for low‐cost applications. Here, lasers emitting in the spectral region between 375 and 475 nm, in which both active material and resonator (1D relief gratings) are based on solution‐processable polymer films, are reported. Ten different organic compounds dispersed in polystyrene are used as active layers of the prepared devices. They include various carbon‐bridged oligo( p ‐phenylenevinylene) (COPV n, with n = 1, 2) derivatives and two terfluorene compounds. The synthesis and complete optical and amplified spontaneous emission properties of one of the COPV1 compounds, COPV1(Me)‐ t ‐Bu, designed for deep‐blue emission, are also included. The feasibility of the resonator fabrication, performed by holographic lithography with a dichromated gelatine photoresist over the active film, is successfully demonstrated for all devices. Remarkably, no resolution limitations are found even for the lowest grating period (235 nm) required for the fabrication of the laser based on COPV1(Me)‐ t ‐Bu. It is also demonstrated that the rectangular grating profile with duty cycle 0.75:0.25 (hill:valley) is very convenient to optimize the resonator efficacy. Abstract : All‐solution‐processed organic distributed feedback lasers, based on top‐layer polymeric resonators, emitting between 375 and 475 nm are reported. Active films are prepared with ten different organic dyes dispersed in polystyrene, including a new compound with deep‐blue emission, COPV1(Me)‐ t ‐Bu, along with its synthesis and optical properties. The top‐layer resonator configuration used shows high performance in all cases.